IMPLEMENTASI ECO-TEOSOFI MASYARAKAT PEDESAAN MELALUI THORIQOH QODIRIYAH NAQSABANDIYAH DALAM MENJAGA LINGKUNGAN HIDUP - Najib, muhammad (AL MURABBI, 2024)
The deepening environmental crisis threatens the survival of humanity, especially in mountainous areas that are vulnerable to natural disasters. This study examines the role of religion from the perspective of Tasawwuf as a solution to increase awareness and environmental conservation actions in the community of Jatiarjo Village, Prigen Pasuruan. The purpose of this study is to focus on the implementation findings of how rural communities that are active in the activities of the Naqsabandiyah Qodiriyah Tarekat succeed in protecting the environment so that they can maintain and operate these natural resources. This study uses a qualitative approach of a descriptive case study. It explores the relationship between the spiritual practice of the Thoriqoh Qodiriyah Naqsabandiyah (TQN) community and natural resource management. The study results show that the spiritual values taught in this institute encourage people to behave environmentally friendly, understand their responsibilities as caliphs, and create harmony between humans and nature. Through practices such as dhikr, gratitude rituals, and the management of organic farming and traditional irrigation systems, the TQN people preserve the environment and strengthen their spiritual identity. These findings also confirm that the integration of eco-theosophical principles can have a positive impact on environmental sustainability and strengthen community bonds in facing the challenges of environmental crises. This research is an additional recommendation and reference for the Sufism community and society, in general, to contribute to developing a more massive spirituality-based environmental preservation concept, especially in rural areas.